Liquid-vapor two-phase flow in centrifugal pump: Cavitation, mass transfer, and impeller structure optimization. (July 2022) - Li, Gaoyang; Ding, Xuhui; Wu, Yubin; Wang, Sirui; Li, Dong; Yu, Wenjin; Wang, Xuezheng; Zhu, Yonghong; Guo, Yuting
Abstract: Computational fluid dynamics (CFD) has been widely used to model the internal flow field of centrifugal pumps to analyze cavitation phenomena. However, accurate determination of cavitation in pumps remains a challenge. In this study, liquid-vapor two-phase flow in centrifugal pump at different conditions and impeller structural parameters were studied numerically and experimentally. Cavitation multiphase unsteady model was proposed to simulate the flow field in the centrifugal pump by CFD method, and an experimental platform was set up to obtain cavitation performance results. The simulation data were validated with experiment and good consistency was achieved. This study investigated the mass transfer and cavitation behavior of centrifugal pumps under various conditions and customizes a simulation process to obtain the optimal combination of impeller blade number, blade wrap angle, and blade installation angle, which was expected to provide helpful insights into the structural optimization design of centrifugal pumps with good cavitation resistance. Highlights: Liquid-vapor two-phase flow in centrifugal pump was carried out. Customized multiphase flow simulation process could guide the design of centrifugal pumps. An experimental platform was fabricated to verify the simulation results. Elucidated mechanism is useful for understanding the cavitation flow. Structural optimization of centrifugal pumps with good cavitation resistance.